Gypsum boards and eggshells facilitate the accumulation of dry matter and nutrients in tomato vegetative structures (Research, Society and Development, 2024)
Gypsum boards, eggshells, and urban pruning residues, when accumulated on sidewalks, vacant lots, or within native forests, can pose risks to public, environmental, and financial health.  This study aimed to assess whether gypsum boards and eggshells could enhance the accumulation of dry matter and nutrients in tomato plants supplemented with Brazilwood leaves as the sole source of nitrogen. The experimental treatments comprised different doses of gypsum boards powder (0, 100, 200, 400, 800, 1600, and 3200 kg ha⁻¹) alongside a single dose of eggshells at 3200 kg ha⁻¹. Following the transplantation of the Caline IPA tomato cultivar into 5-liter pots, the experiment was conducted in a randomized block design with four replications. Growth indicators and macronutrient content were evaluated at 52 days post-emergence. The lower doses of gypsum boards powder, specifically 100, 200, and 400 kg ha⁻¹, demonstrated over a twofold increase in dry biomass and macronutrient content compared to the control treatment. The doses of 800, 1600, and 3200 kg ha⁻¹ resulted in more than an eightfold increase, with the 800 kg ha⁻¹ dose being particularly notable for promoting an increase of over thirteen times in these variables. Eggshells increased the number of leaves by 40% and more than doubled both dry biomass and nutrient content. This study suggests that gypsum boards powder, eggshells, and Brazilwood leaves can enhance tomato yield in low-nutrient input systems.